**Solve the Equation: 6x - 4(3 - 2x) = 5(x - 4) - 10**

In this article, we will solve the equation 6x - 4(3 - 2x) = 5(x - 4) - 10.

### Step 1: Simplify the Left-Hand Side

Let's start by simplifying the left-hand side of the equation:

6x - 4(3 - 2x) = 6x - 12 + 8x

Combine like terms:

6x + 8x - 12 = 14x - 12

### Step 2: Simplify the Right-Hand Side

Now, let's simplify the right-hand side of the equation:

5(x - 4) - 10 = 5x - 20 - 10

Combine like terms:

5x - 30

### Step 3: Equate the Two Expressions

Now that we have simplified both sides of the equation, let's equate them:

14x - 12 = 5x - 30

### Step 4: Solve for x

Add 12 to both sides of the equation:

14x = 5x - 18

Subtract 5x from both sides:

9x = -18

Divide both sides by 9:

x = -2

Therefore, the solution to the equation 6x - 4(3 - 2x) = 5(x - 4) - 10 is **x = -2**.